The Trade and Mestizo Culture Effect in Ternate - M. Ridha Ajam; Irfan Ahmad (Syntax Corporation Indonesia, 2022)
This study discusses the spice (clove) trade in Ternate in the XV-XVII centuries by Arab, Chinese, Malay, Javanese, Makassar, Portuguese, Spanish, Dutch and English traders. The importance of clove commodities in Ternate in trading activities makes Ternate one of the international trade networks. This research uses the method of historical science and the study of multiculturalism. The research location is in Ternate City, North Maluku Province. The results showed that Ternate played an essential role in trading activities as a maritime kingdom. The spice route is not just a commodity trading route but also a commercial process that allows the exchange of values and cultures that have helped shape the identity of the Ternate community today. The impact of culture can be found in language, clothing, art, food, and settlements. In other words, the clove trade involving various nations in Ternate also brought together cultures